Food restriction in hybrid catfish Pseudoplatystoma reticulatum x Leiarius marmoratus produced in cages: zootechnical performance, physiological metabolism and economic viability - Acunha, Rubia Mara Gomes; Simões, Andre Rozemberg Peixoto; Oliveira, Fúlvia Cristina; Fernandes, Carlos Eurico dos Santos; Soares, Michelly Pereira; Barros, Adriana Fernandes; Rodrigues, Robson Andrade; Campos, Cristiane Meldau (Acta Scientiarum. Animal Sciences, 2025)
Production of the hybrid Pseudoplatystoma reticulatum x Leiarius marmoratus submitted to food restriction and re-alimentation was evaluated on commercial fish farming for zootechnical performance, physiological metabolism and economic viability. For 60 days, hybrid catfish (n=312; 562±12.00 g; 40±3.30 cm) were maintained in cages with a density of 13 fish m3. Experimental design was totally randomized with two feeding strategies: (FR15/RE15) food restriction for 15 days, followed by re-alimentation for 15 days; (NR) no food restriction and three repetitions. Biometry was performed twice a month to determine zootechnical levels. Blood samples were collected for hematologic and biochemical analysis; and liver and intestine to determine hepatosomatic index (HSI), hepatocytes histometry and intestinal coefficient (IC). For the economic evaluation, we used the Total Operational Cost. Fish from FR15/RE15 exhibited total compensatory gain. IC and HIS were superior in FR15/RE15 at 60 days. Hematocrit, hemoglobin and erythrocyte count exhibited increased levels on FR15/RE15 at 30 and 45 days. Exposure to FR15/RE15 influenced hepatocytes histometry. Both feeding systems showed economic viability in short and long-term when fish density was 60 fish m-3. Food restriction for 15 days and re-alimentation for 15 days is indicated for hybrid catfish production in cages on market conditions.